Preparation method of light-emitting diode with inverted structure
By using plasma gas cleaning and segmented deposition of AL2O3 during the ALD deposition of light emitting diodes, the problem of water absorption and rupture of DBR flip structure in high temperature and high humidity environment is solved, and a low-cost and high-efficiency light emitting diode preparation is achieved, avoiding the problem of low 1ua current opening voltage.
Patent Information
- Application Number
- CN202411720080.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The DBR flip structure is prone to absorb water vapor and breakage in high temperature and high humidity environments. The existing technology is difficult to effectively solve this problem. At the same time, the ALD deposition of AL2O3 has the problem of low 1ua current opening voltage.
A flip-structured light emitting diode preparation method is adopted. The GAN surface is cleaned by N2, N2O or O3 plasma before ALD deposition, and AL2O3 is deposited in combination with TMAL and H2O reactions, and the AL2O3 film layer is divided into multiple segments, and plasma gas is used to clean it to form a low-cost and high-efficiency light emitting diode.
It realizes a light-emitting diode that is not easy to absorb water vapor rupture in high temperature and high humidity environments, and solves the problem of low 1ua current opening voltage, ensuring production cost and efficiency.
Smart Images

Figure CN119677248A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of light emitting diodes, and in particular relates to a method for preparing a flip-chip structure light emitting diode. Background Art
[0002] DBR flip-chip structure products use electron beam evaporated DBR as the reflective layer and insulating layer. The DBR materials are mainly SiO2 and Ti3O5. Due to the water absorption and density of the material, DBR easily absorbs water vapor in the air, thus breaking and failing during long-term high temperature and high humidity aging.
[0003] In order to solve the problem of DBR rupture due to absorption of water vapor in high temperature and high humidity environment, the industry introduced the composite structure of PECVD plasma enhanced chemical vapor deposition method to form SiO2 film and combined with ALD atomic layer deposition AL2O3 to improve the influence of water vapor in the environment on the DBR film layer of the product structure. ALD atomic layer deposition is a method that can coat a substance layer by layer on the surface of a substrate in the form of a single atomic film. It exposes a variety of gas phase raw materials (precursors) alternately to the surface of the substrate to form a film. Unlike CVD, different types of precursors do not enter the reaction chamber at the same time, but are introduced (pulsed) and discharged (purge) as independent steps. In each pulse, the precursor molecules act in a self-controlled manner on the surface of the substrate, and the reaction ends when there are no adsorbable sites on the surface.
[0004] There are two schemes for ALD deposition of AL2O3: the first is the reaction of TMAL (trimethylaluminum) and H2O as two reaction sources to generate AL2O3. This scheme has a short film production cycle and low cost, but there are -OH groups and charge residues at the contact interface between AL2O3 and GAN, resulting in the problem of low turn-on voltage at a small current of 1ua on the chip; the second is the reaction of TMAL and O3 to generate AL2O3. In this scheme, there is basically no charge residue at the contact interface between AL2O3 and GAN, and there is no problem of low turn-on voltage at a small current of 1ua, but the production cycle is long and the cost is high. Summary of the invention
[0005] In view of the problems in the background technology, the present invention has developed a method for preparing a flip-chip structure light-emitting diode, which can produce a low-cost, high-efficiency light-emitting diode with a small current turn-on voltage of 1ua and no leakage.
[0006] To achieve the above object, the present invention adopts the following technical solutions: A method for preparing an inverted structure light emitting diode comprises the following steps: (1) Fabrication of epitaxy on patterned sapphire substrates, including N-GAN, quantum well, and P-GAN; (2) Make MESA and etch out the N-type area; (3) Making ISO to etch the middle part of the cutting path into the patterned sapphire substrate; (4) Making a transparent conductive layer: Making a planar or graphic mesh distribution or island distribution, making ohmic contact with P-GaN. (5) Making metal electrode 1: divided into P region and N region, the P region is connected to the transparent conductive layer on the P-GaN, and the N region is connected to the N-GaN; (6) Cleaning before ALD deposition: Use plasma gas to clean the GAN side exposed by MESA etching; (7) ALD deposition of AL2O3: 1) ALD deposition of AL2O3, the first 10-100 pulse cycles use TMAL and O3 as reaction sources, and subsequent film formation uses TMAL and H2O reaction; 2) Using TMAL and H2O to react and deposit AL2O3, the entire film layer is divided into 2-10 sections, and plasma gas is used for cleaning between the two sections; (8) PECVD deposition of SiO2; (9) Electron beam evaporation coating DBR: Two layers with different refractive indices are deposited alternately to form a Bragg reflector layer; (10) DBR through hole: Etch through holes through DBR, SiO2, and AL2O3 to leak out the P and N regions of metal electrode 1 respectively; (11) Fabrication of metal electrode 2: divided into P region and N region. Through the connection holes made on the DBR, the P region is connected to the metal electrode - P region; the N region is connected to the metal electrode - N region.
[0007] Preferably, the transparent electrode in step (4) is made of ITO or ZnO material with a thickness of 5nm-200nm.
[0008] Preferably, in step (5), the electrode 1 comprises an adhesion layer and a structural layer, the adhesion layer is CR / NI / TI, the structural layer is AL / TI / PT / NI / AU, and the total thickness is 50nm-5000nm.
[0009] Preferably, in step (6), the plasma gas is N2O, N2 or O3, the gas flow rate is 5-500sccm, the power is 10-500W, and the time is 10S-1000S.
[0010] Preferably, the plasma gas in step (7) is N2 or N2O.
[0011] Preferably, the entire ALD layer of step (7) has a thickness of 45-300 nm, which is divided into 2-10 segments, and the segments are evenly segmented or the thickness of each of the first three segments is 2-15 nm, and the thickness of each of the last segments is 10-100 nm. The segmentation with a low thickness in the front segment and a high thickness in the back segment can solve the problems of residual ions and charges in the film deposition and residual ions due to insufficient reaction in the film layer, improve the insulation of the bottom layer, and avoid the current verification of the AL2O3 and GaN interface passing through, causing small current micro leakage.
[0012] Preferably, in step (8), the PECVD deposition of SiO2 has a thickness of 50-1000 nm and a temperature of 150-300°C.
[0013] Preferably, the step (9) uses two film layers with different refractive indices, SiO2 and Ti3O5, to be deposited alternately; the temperature is 150-300°C, the thickness is 1000-5000nm, and the number of film layers is 20-60.
[0014] Preferably, in step (11), the electrode 2 comprises an adhesion layer, a structural layer and a eutectic layer. The adhesion layer is CR / NI / TI with a thickness of 0.5-100 nm, the structural layer is AL / TI / PT / NI / AU metal with a thickness of 1000-5000 nm, and the eutectic layer is Au, Sn, AnSn alloy, Sn ball with a thickness of 1 um-100 um.
[0015] Preferably, in the step (7) ALD deposition of AL2O3, AL2O3 is replaced by HfO2. Specifically, 1) ALD deposition of HfO2 uses TDMAHf and O3 as reaction sources in the first 10-100 pulse cycles, and subsequent film formation uses TDMAHf and H2O reaction; 2) HfO2 is deposited by using TDMAHf and H2O reaction, and the entire film layer is divided into 2-10 sections, and plasma gas is used for cleaning between two sections; the dielectric constant of AL2O3 is 9.8, and the dielectric constant of HfO2 is 18, and the latter has better insulation properties.
[0016] Compared with the prior art, the present invention has the following beneficial effects: (1) Before ALD deposition of AL2O3, use N2, N2O or O3 plasma to clean the GAN surface, improve the cleanliness of the GAN MESA side, eliminate residual ions and groups on the side, and then use TMAL and H2O to react and deposit the film to improve the low turn-on voltage problem of 1ua small current; (2) ALD deposition of AL2O3, the first 10-100 pulse cycles use TMAL and O3 as reaction sources to solve the -OH group and charge residue problems at the interface between GAN and AL2O3. The subsequent film formation uses TMAL and H2O reaction, which not only meets the 1ua low current turn-on voltage problem, but also ensures production cost and efficiency; (3) TMAL and H2O were used to react and deposit AL2O3, and the entire film layer was divided into 2-10 sections. N2 or N2O plasma was used to clean between the two sections to eliminate the residual ions and charges at the interface between AL2O3 and GAN and the residual ions in the film layer due to insufficient reaction, thereby improving the low start-up voltage problem at a small current of 1 ua. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 Schematic diagram of the DBR composite membrane structure.
[0018] Figure 2 This is a schematic diagram of the structure of one embodiment of an AL2O3 film layer. DETAILED DESCRIPTION
[0019] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation mode, structure, characteristics and effects of the present invention are described in detail below in combination with the accompanying drawings and preferred embodiments.
[0020] Embodiment 1: A method for preparing a flip-chip structure light-emitting diode, comprising the following steps: 1. Epitaxy is produced on patterned sapphire substrates, including N-GAN, quantum well, and P-GAN.
[0021] 2. Make MESA and etch out the N-type area.
[0022] 3. Make ISO to etch the middle part of the cutting path to the patterned sapphire substrate.
[0023] 4. Make a transparent conductive layer: It can be made into a planar or graphic mesh distribution or island distribution, and make ohmic contact with P-GaN. The transparent electrode is made of ITO, ZnO and other materials with a thickness of 5nm-200nm.
[0024] 5. Make metal electrode 1: It is divided into P region and N region. The P region is connected to the transparent conductive layer on P-GaN, and the N region is connected to N-GaN. Electrode 1 has an adhesion layer and a structural layer. The adhesion layer is CR / NI / TI, etc., and the structural layer is AL / TI / PT / NI / AU, etc. The total thickness is 50nm-5000nm.
[0025] 6. Cleaning before ALD deposition: Use N2O or N2 or O3 plasma to clean the GAN side exposed by MESA etching, eliminate GAN side contamination and residual ions, reduce the probability of micro-leakage on the GAN side under a small current of 1ua, and the problem of low start-up voltage at a small current of 1ua; the cleaning gas flow rate is 5-500sccm, the power is 10-500W, and the time is 10S-1000S.
[0026] 7. ALD deposition of AL2O3: 1) ALD deposition of AL2O3, the first 10-100 pulse cycles use TMAL and O3 as reaction sources to solve the -OH group and charge residue problems at the interface between GAN and AL2O3. The subsequent film formation uses TMAL and H2O reaction, which not only meets the problem of low turn-on voltage at a small current of 1ua, but also ensures production cost and efficiency; 2) Use TMAL and H2O to react and deposit AL2O3, divide the entire film into 2-10 sections, and use N2 or N2O plasma to clean between the two sections to eliminate the residual ions and charges on the interface between AL2O3 and GAN and the residual ions in the film layer that are not fully reacted, and improve the problem of low turn-on voltage at a low current of 1ua; the sections can be evenly divided, or the thickness of the first 1-3 sections can be relatively low (such as Figure 2 as shown).
[0027] 8. PECVD deposition of SiO2: thickness 50-1000nm, temperature 150-300℃; 9. Electron beam evaporation coating DBR: Two films with different refractive indices such as SiO2 and Ti3O5 can be deposited alternately to form a Bragg reflector film (such as Figure 1 As shown); temperature 150-300°C, thickness 1000-5000nm, number of film layers 20-60 layers.
[0028] 10. DBR through hole: Etch a through hole through the DBR, SiO2, and AL2O3 to leak out the P region and N region of the metal electrode one respectively.
[0029] 11. Make metal electrode 2: It is divided into P region and N region. Through the connection holes made on DBR, the P region is connected to metal electrode 1 P region; the N region is connected to metal electrode 1 N region; electrode 2 has an adhesion layer, a structural layer, and a eutectic layer. The adhesion layer is CR / NI / TI with a thickness of 0.5-100nm, the structural layer is AL / TI / PT / NI / AU and other metals with a thickness of 1000-5000nm, and the eutectic layer is Au, Sn, AnSn alloy, Sn ball with a thickness of 1um-100um.
[0030] Embodiment 2: A method for preparing a flip-chip structure light-emitting diode, comprising the following steps: 1. Epitaxy is produced on patterned sapphire substrates, including N-GAN, quantum well, and P-GAN.
[0031] 2. Make MESA and etch out the N-type area.
[0032] 3. Make ISO to etch the middle part of the cutting path to the patterned sapphire substrate.
[0033] 4. Make a transparent conductive layer: It can be made into a planar or graphic mesh distribution or island distribution, and make ohmic contact with P-GaN. The transparent electrode is made of ITO, ZnO and other materials with a thickness of 5nm-200nm.
[0034] 5. Make metal electrode 1: It is divided into P region and N region. The P region is connected to the transparent conductive layer on P-GaN, and the N region is connected to N-GaN. Electrode 1 has an adhesion layer and a structural layer. The adhesion layer is CR / NI / TI, etc., and the structural layer is AL / TI / PT / NI / AU, etc. The total thickness is 50nm-5000nm.
[0035] 6. Cleaning before ALD deposition: Use N2O or N2 or O3 plasma to clean the GAN side exposed by MESA etching, eliminate GAN side contamination and residual ions, reduce the probability of micro-leakage on the GAN side under a small current of 1ua, and the problem of low start-up voltage at a small current of 1ua; the cleaning gas flow rate is 5-500sccm, the power is 10-500W, and the time is 10S-1000S.
[0036] 7. ALD deposition of HfO2: 1) ALD deposition of HfO2, the first 10-100 pulse cycles use TDMAHf and O3 as reaction sources to solve the -OH group and charge residue problems at the interface between GAN and HfO2. The subsequent film formation uses TDMAHf and H2O reaction, which not only meets the problem of low turn-on voltage at a small current of 1ua, but also ensures production cost and efficiency; 2) Use TDMAHf and H2O to react and deposit HfO2, divide the entire film layer into 2-10 sections, and use N2 or N2O plasma to clean between the two sections to eliminate the residual ions and charges on the interface between HfO2 and GAN and the residual ions in the film layer that are not fully reacted, and improve the problem of low turn-on voltage at a small current of 1ua; the sections can be evenly divided, or the thickness of the first 1-3 sections can be relatively low.
[0037] 8. PECVD deposition of SiO2: thickness 50-1000nm, temperature 150-300℃; 9. Electron beam evaporation coating DBR: Two films with different refractive indices such as SiO2 and Ti3O5 can be alternately deposited to form a Bragg reflection film layer; the temperature is 150-300℃, the thickness is 1000-5000nm, and the number of film layers is 20-60.
[0038] 10. DBR through hole: Etch a through hole through the DBR, SiO2, and HfO2 to leak out the P region and N region of the metal electrode one respectively.
[0039] 11. Make metal electrode 2: It is divided into P region and N region. Through the connection holes made on DBR, the P region is connected to metal electrode 1 P region; the N region is connected to metal electrode 1 N region; electrode 2 has an adhesion layer, a structural layer, and a eutectic layer. The adhesion layer is CR / NI / TI with a thickness of 0.5-100nm, the structural layer is AL / TI / PT / NI / AU and other metals with a thickness of 1000-5000nm, and the eutectic layer is Au, Sn, AnSn alloy, Sn ball with a thickness of 1um-100um.
[0040] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a flip-chip structure light-emitting diode, characterized in that: The following steps are involved: (1) Fabrication of epitaxy on patterned sapphire substrates, including N-GAN, quantum well, and P-GAN; (2) Make MESA and etch out the N-type area; (3) Making ISO to etch the middle part of the cutting path into the patterned sapphire substrate; (4) Making a transparent conductive layer: Making a planar or graphic mesh distribution or island distribution, making ohmic contact with P-GaN. (5) Making metal electrode 1: divided into P region and N region, the P region is connected to the transparent conductive layer on the P-GaN, and the N region is connected to the N-GaN; (6) Cleaning before ALD deposition: Use plasma gas to clean the GAN side exposed by MESA etching; (7) ALD deposition of AL2O3: 1) ALD deposition of AL2O3, the first 10-100 pulse cycles use TMAL and O3 as reaction sources, and subsequent film formation uses TMAL and H2O reaction; 2) Using TMAL and H2O to react and deposit AL2O3, the entire film layer is divided into 2-10 sections, and plasma gas is used for cleaning between the two sections; (8) PECVD deposition of SiO2; (9) Electron beam evaporation coating DBR: Two layers with different refractive indices are deposited alternately to form a Bragg reflector layer; (10) DBR through hole: Etch through holes through DBR, SiO2, and AL2O3 to leak out the P and N regions of metal electrode 1 respectively; (11) Fabrication of metal electrode 2: divided into P region and N region. Through the connection holes made on the DBR, the P region is connected to the metal electrode - P region; the N region is connected to the metal electrode - N region.
2. A method for preparing a flip-chip structure light-emitting diode according to claim 1, characterized in that: The transparent electrode in step (4) is made of ITO or ZnO material with a thickness of 5nm-200nm.
3. The method for preparing a flip-chip structure light emitting diode according to claim 1, characterized in that: In the step (5), the electrode 1 comprises an adhesion layer and a structural layer, wherein the adhesion layer is CR / NI / TI, and the structural layer is AL / TI / PT / NI / AU, with a total thickness of 50nm-5000nm.
4. A method for preparing a flip-chip structure light emitting diode according to claim 1, characterized in that: In the step (6), the plasma gas is N2O, N2 or O3, the gas flow rate is 5-500sccm, the power is 10-500W, and the time is 10S-1000S.
5. The method for preparing a flip-chip structure light emitting diode according to claim 1, characterized in that: In the step (7), the plasma gas is N2 or N2O.
6. The method for preparing a flip-chip structure light emitting diode according to claim 1, characterized in that: The entire ALD layer of step (7) has a thickness of 45-300 nm, which is divided into 2-10 segments, and the first three segments are uniformly segmented or each segment has a thickness of 2-15 nm, and the thickness of each segment of the last segment is 10-100 nm.
7. The method for preparing a flip-chip structure light emitting diode according to claim 1, characterized in that: In the step (8), PECVD deposits SiO2 with a thickness of 50-1000 nm and a temperature of 150-300° C.
8. The method for preparing a flip-chip structure light emitting diode according to claim 1, characterized in that: The step (9) uses SiO2 and Ti3O5 film layers with different refractive indices to be deposited alternately; the temperature is 150-300°C, the thickness is 1000-5000nm, and the number of film layers is 20-60.
9. The method for preparing a flip-chip structure light emitting diode according to claim 1, characterized in that: In the step (11), the electrode 2 comprises an adhesion layer, a structural layer and a eutectic layer. The adhesion layer is CR / NI / TI with a thickness of 0.5-100 nm, the structural layer is AL / TI / PT / NI / AU metal with a thickness of 1000-5000 nm, and the eutectic layer is Au, Sn, AnSn alloy, Sn ball with a thickness of 1 um-100 um.
10. A method for preparing a flip-chip structure light emitting diode according to claim 1 or 6, characterized in that: In the step (7), AL2O3 is replaced by HfO2 in the ALD deposition of AL2O3. Specifically, 1) ALD deposition of HfO2 uses TDMAHf and O3 as reaction sources in the first 10-100 pulse cycles, and subsequent film formation uses TDMAHf and H2O reaction; 2) HfO2 is deposited by using TDMAHf and H2O reaction, and the entire film layer is divided into 2-10 sections, and plasma gas is used for cleaning between two sections.
Citation Information
Patent Citations
Sapphire pattern substrate structure capable of improving luminous efficiency of GaN-based LED
CN108598232A
Miniature light-emitting element and manufacturing method thereof
CN113451476A
Light emitting diode chip and preparation process thereof
CN114420816A
Flip mini-LED chip and preparation method thereof
CN117497653A
Preparation method of flip LED chip
CN117747719A